2016
DOI: 10.1021/acs.jpcc.6b04114
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Photoinduced Charge Transfer Dynamics of Single Perylenediimide Dyes in a Polymer Matrix by Bin-Time Dependence of their Fluorescence Blinking Statistics

Abstract: Fluorescence on−off blinking of single perylenediimide (DMP−PDI) dyes embedded in a disordered matrix of poly(methyl methacrylate) (PMMA) was investigated by single-molecule fluorescence spectroscopy. In particular, we examined the bin-time dependencies of the complementary cumulative distribution functions (cCDF) of the on-time and off-time durations. It appears that intersystem crossing (ISC) within DMP−PDI competes with charge transfer between DMP−PDI and PMMA. The single-molecule and ensemble cCDFs of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 57 publications
6
42
0
Order By: Relevance
“…Although power-law behavior is often reported in blinking studies 8,9,26 and has been reported for delayed luminescence as well, 1,4,5 deviations from power-law have been emphasized in recent blinking literature. [27][28][29] Deviations from power-law kinetics are clearly evident in the delayed luminescence kinetics reported here. For both delayed luminescence (this study) and some blinking data, [27][28][29] log-normal distributions reproduce the dynamics better than power-law distributions.…”
Section: Discussionmentioning
confidence: 55%
“…Although power-law behavior is often reported in blinking studies 8,9,26 and has been reported for delayed luminescence as well, 1,4,5 deviations from power-law have been emphasized in recent blinking literature. [27][28][29] Deviations from power-law kinetics are clearly evident in the delayed luminescence kinetics reported here. For both delayed luminescence (this study) and some blinking data, [27][28][29] log-normal distributions reproduce the dynamics better than power-law distributions.…”
Section: Discussionmentioning
confidence: 55%
“…Our experimental results indicate that (i) the transition rates k 23 and k 31 are not constants, and their variability due to variations in the local nanoenvironment must be taken into account and (ii) the acceptor addition changes the environment in such a way that affects the rate k 23 . The nature of transition to longlived dark states inferred from blinking statistics of molecules incorporated into polymer matrices has been discussed in the literature, 10,12,17 with charge transfer to acceptor states in the polymer resulting in a change from a fluorescent parent molecule to a non-fluorescent radical ion as a possible mechanism. Given that in our experiments the Pn-TCHS-F8 single molecule reporters are positioned at least 3 nm away from the nearest IF-TIPS acceptor molecule, the observed effect of the IF-TIPS addition (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of experimental single-molecule fluorescence trajectories has enabled better understanding of energy and charge transfer processes between the photoexcited molecule and other molecules in the surrounding environment. [7][8][9][10] However, due to complexity of the nanoscale environment, quantitative assessment of structureproperty relationships is challenging. In order to gain physical insight into the dynamics of the nanoscale interactions, Monte Carlo simulations have been utilized to model the charge carrier transitions that determine the experimentally measured fluorescence time trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, understanding of energy and charge transfer processes between the photoexcited molecule and other molecules in the surrounding environment during the molecule degradation and recovery is difficult due to complexity of the nanoscale environment. [8][9][10][11] To aid in the interpretation of the data, Monte Carlo simulations have been utilized to model fluorescence time trajectories that are affected by these processes. [12][13][14][15] In particular, we seek to further refine the model and to determine the accuracy of the single molecule analysis used in experimental data processing.…”
Section: -S R= Nodipsmentioning
confidence: 99%